"Can I Hit Our JUUL?": The Norms of Vaping and Dating among Emerging Adults. Issue 5 (16th April 2023) - Hernandez, Rachael; Ranjit, Yerina; Collins, Chandrika C.
ABSTRACT: The growing popularity of vaping devices is of major concern for public health practitioners, and personal relationships have the potential to either increase or decrease the use of vaping devices. The escalation of romantic relationships, in particular, can have implications for the use of vaping devices. The current study seeks to understand how emerging adults negotiate communication about the use of vaping devices while initiating and escalating romantic relationships. Five focus groups were conducted with groups of participants who either did or did not use vaping devices. Results reveal the various reasons participants were reluctant to date individuals who vaped and illustrated the role of vaping norms in the stages of relational escalation. Practical and theoretical implications are discussed.